A novel cascaded control to improve stability and inertia of parallel buck-boost converters in DC microgrid. (July 2020) - Cheng, Zhiping; Li, Zhongwen; Li, Shuihui; Gao, Jinfeng; Si, Jikai; Das, Himadry Shekhar; Dong, Weizhen
Highlights: NTSMC-based cascaded control for a DC/DC converter to increase the robustness. A VIC method to increase the inertia of the DC/DC converter-interfaced DG unit. Synchronization control to satisfy the plug-and-play of a buck-boost converter. Hardware experimental results demonstrate the improved performance. Abstract: To deal with the issues caused by the high integration of renewable resources, the parallel operation of the converters is generally required to improve the system stability and reliability. To support the parallel operation of buck-boost DC/DC converters, they are generally regulated by a cascaded control strategy, which includes droop control loop, and nested proportional-integral (PI) based voltage and current control loops. However, it can provide barely inertia support and needs precise system model to reach the desired performance. In order to overcome these drawbacks, this paper proposes a novel cascaded control strategy for parallel operation of buck-boost DC/DC converters. The proposed cascaded control strategy involves a voltage synchronization loop, a virtual inertia control (VIC) loop, and two nested NTSMC based voltage and current control loops. The voltage synchronization controller can enable the plug and play requirements by synchronizing the output voltage of the converter with the voltage at the point of common coupling (PCC) before connecting a DC/DC converter to the DC microgrid. The VIC can improve the inertia of the converter-interfaced DGs. The nested-loop NTSMC based voltage and current controller can improve the robustness of converter system. Hardware experiments demonstrate the improved performance of the proposed control strategy.